Financial transparency: a scale development study - Koochel, Emily (Kansas State University, 2017)
Interpersonal aspects of a relationship (i.e., equality, trust, disclosure, etc.) as they relate to finances have important implications for marital satisfaction; however, emphasis on financial transparency, “the open and honest disclosure of one’s finances,” has yet to be researched. To increase our capacity to study the role of finances in the marital relationship, the purpose of this study was to develop the Financial Transparency Scale (FTS) to assess financial transparency between married partners. A sample of 183 married individuals in their first 5 years of their first marriage completed an online survey, consisting of the FTS and four related scales. Principal components analysis (PCA) was conducted to determine the FTS is comprised of three components: financial partnership, financial secrecy, and financial trust and disclosure of the individual partner. The first component, financial partnership (eigenvalue = 10.909), consisted of 18 items and accounted for 41.96% of the variance and had a high internal reliability of (α = .95). Component 2, financial secrecy (eigenvalue = 2.845), consisted of three items and accounted for 10.94% of variance with an internal reliability of (α = .93). Component 3, financial trust and disclosure of the individual partner (eigenvalue = 1.76), consisted of five items and accounted for 6.77% of total variance with an internal reliability (α = .83). The FTS was positively correlated with four related scales: the Kansas Marital Satisfaction Scale, the Shared Goals and Values Scale, the Frequency of Financial Management Scale, and the Communication Patterns Questionnaire – Short Form, each of which are key behaviors of financial and marital satisfaction. The FTS will benefit financial practitioners as they can use the scale to determine the level of financial transparency between married individuals, drawing attention to areas of concern such as financial secrecy between partners. For researchers, this scale provides a measurement for a sophisticated perspective on the interpersonal factors that mediate financial transparency between married individuals.
Keywords: Marriage; Self-disclosure; Financial secrecy; Communication; Marital satisfactionFinancial transparency